The Influence of Soccer Skill Level in the Learning of a Novel Balance task - Konstadakos, Στυλιανός; Zaxariadis, Πραξιτέλης; Karaiosif, Αλέξανδρος; Hatzitaki, Βασιλεία (Inquiries in Physical Education and Sport, 2004)
The present study examined whether expertise in soccer affects the performance and learning of a novel task requiring continuous postural adjustments to dynamic visual information. A group of 10 soccer experts (mean age: 21.4±1.7, training years: 8.6±3) and 10 age-matched controls (mean age: 20.4, ±0.8) were asked to stand on two adjacent force platforms (ERBE BALANCE SYSTEM), while on-line visual feedback about each foot’s force vector was provided on a computer screen ahead of them. The aim of the task was to shift weight between sides so as to always maintain each foot’s vector within the visually specified force constraints. Training consisted of 3 blocks of 5 trials separated by 1-minute intervals and followed by 5 retention trials (24 hours after training). Learning was reflected in the mean movement time (MT) and number of errors (E) calculated over the 5-trial blocks. Soccer experts exhibited significantly less number of left side errors (p<0.05) more stable performance (p<0.05) and learned the specific task faster compared to untrained individuals (p<0.05). It is concluded that specific soccer training reinforces perception-action coupling in postural tasks facilitating learning of tasks requiring on-line linking of optical information to motor commands.